2018
DOI: 10.1108/ijlm-12-2016-0297
|View full text |Cite
|
Sign up to set email alerts
|

Ensuring supplier participation toward addressing sustainability-oriented objectives of the mid-day meal supply chain

Abstract: Purpose The purpose of this paper is to explore and further explain the phenomena of supplier participation in addressing the sustainability-oriented objectives of a supply chain. Specifically, the paper explains how a buyer can integrate sustainability concerns among its suppliers. The study is based in the context of the Indian school feeding (mid-day meal) program and approaches the issue from the perspective of a mid-day meal provider. Design/methodology/approach This paper first explains how the mid-day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 75 publications
(98 reference statements)
0
15
0
Order By: Relevance
“…According to Chen et al (2017), collaboration involves information sharing, strategic alliance, performance and cost reduction. Collaboration became essential for SC integration, especially within buyer-supplier relationships (Kanyoma et al , 2018; Ralston et al , 2017; Roy et al , 2018). In our research, we found that the cooperative requires more collaborative behaviours of its members, which happens through daily practices.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Chen et al (2017), collaboration involves information sharing, strategic alliance, performance and cost reduction. Collaboration became essential for SC integration, especially within buyer-supplier relationships (Kanyoma et al , 2018; Ralston et al , 2017; Roy et al , 2018). In our research, we found that the cooperative requires more collaborative behaviours of its members, which happens through daily practices.…”
Section: Discussionmentioning
confidence: 99%
“…for-profit focal companies) request changes in their SCs not only concerning sustainability standards implementation, but also on how their SC members are engaged to jointly develop these changes. This process of spreading sustainability requires a strong SC relationship, which generates compliance and commitment among SC members (Roy et al , 2018; Ramirez et al , 2020). Although spreading and diffusion are often seen as complementary, they do have different meanings.…”
Section: Extending Sustainability To Sc Membersmentioning
confidence: 99%
“…Among Asian countries, one study was identified in Japan [ 35 ] and one in India [ 72 ]. In Japan [ 35 ], the study demonstrated that the reinforcement of social norms not to waste and factors related to the planning of menus, pedagogical practices, and recycling and composting activities, contributed to reducing the food waste in schools.…”
Section: Resultsmentioning
confidence: 99%
“…The literature generally advocates the inclusion of consumer-oriented safety-quality metrics in performance management systems to augment the traditional food chain goals of efficiency, flexibility and responsiveness (Aramyan et al, 2007). However (in interaction 35), Roy et al (2018a) broaden consumer emphasis by maintaining that it is the focal food firm's responsibility to: first, internalize the end consumers' safetyquality interests in its organizational operations as a cultural agenda; second, transform its functional units; and third, facilitate an inter-firm boundary spanning throughout the food chain to ensure a chain-wide emphasis on the end consumers' safety-quality preferences.…”
Section: Theme 3: Supply Chain Integration On the Agenda Of Food Chain Integritymentioning
confidence: 99%